Steps toward understanding the impact of early emotional experiences on disordered eating: The role of self-criticism, shame, and body image shame - Góis, Ana Carolina Figueiredo da Costa (2017)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação